Detection of Genetic Modified Feed Component - H. Younis, Mohammed; Q. Younan, Hayba; H. Khudhair, Saad; L. Aarif, Ghaith; R. Abdulha, Heba; R. Abdulha, Heba (Iraqi Journal of Science, 2023)
There are growing concerns over the possibility of transfer genetically modifiedsequences from genetically modified feed component (GM feed) to animals andtheir products, moreover, affect these sequences on animal and human health. Thisstudy was implemented to detect P35S in modified feed by using PCR technique bydetecting presence P35S promoter, which responsible for the regulation of geneexpression for most of the transgenic genes. Thirty eight feed samples werecollected from different sources of Baghdad markets, which have been used forfeeding livestock, comprise 21 coarse mixes feed, 13 pelleted feed, and 4 expandedfeed. Genomic DNA was extracted by using two methods, CTAB method andWizard kit. In order to verify the presence (P35S) in feed samples, a pair of primerfor 35S promoter was used. The results of the present study showed that 58% oftested samples contained promoter P35S this means presence genetically modifiedfeed in the Baghdad market